Impact Analysis of the Influence of Institutional Capacity and the Use of Performance-Based Budgeting on Original Regional Revenue Receipts in the Tanggerang Regency Area - Firzada, Ashrof F.; Akbar, Bahrullah; Ilham, Muh.; Kawuryan, Megandaru W. (Universitas Medan Area, 2024)
This study aims to analyze the impact of institutional capacity and the use of performance-based budgeting on local revenue (PAD) in the Tangerang Regency area. This research uses a quantitative descriptive analysis method using secondary data obtained from various trusted sources. This research identifies institutional capacity, which includes aspects of human resources, institutional systems, and managerial capacity, and analyzes the implementation of performance-based budgeting to increase PAD revenues. The results of the analysis show that strong institutional capacity significantly contributes to increasing PAD revenues. Apart from that, the use of performance-based budgeting has also been proven to have a positive impact on PAD revenues. The implication of this research is the importance of increasing institutional capacity and implementing performance-based budgeting effectively as a strategy to increase PAD revenues in Tangerang Regency. This study makes an important contribution in the context of regional financial development and public financial management, as well as providing a basis for more effective policymaking in increasing regional income.